Homogeneous versus Heterogeneous Catalysts in Water Oxidation. Issue 4 (23rd August 2013) - Fukuzumi, Shunichi; Hong, Dachao
Abstract: Recent developments in thermal and photochemical water oxidation by using homogeneous and heterogeneous catalysts is described together with the conversion of the homogeneous catalysts into heterogeneous catalysts during the course of water oxidation. The use of homogeneous catalysts is advantageous in the elucidation of detailed catalytic mechanisms including the detection of active intermediates for water oxidation. In contrast, heterogeneous catalysts are advantageous for practical applications, because of their high catalytic activity and the ease with which they can be separated by filtration. However, it is quite difficult to identify the active intermediates on the surfaces of heterogeneous catalysts, and therefore, the heterogeneous catalytic mechanism of water oxidation has not been clarified. Although investigations on homogeneous and heterogeneous catalysts for water oxidation have been performed rather independently, the link between homogeneous and heterogeneous catalysts is becoming more important for the development of efficient WOCs. This microreview focuses on factors to determine if the actual catalysts for water oxidation are homogeneous or heterogeneous depending on the conditions under which the catalysts are used. Ligand oxidation of homogeneous catalysts sometimes results in dissociation of the ligands to form nanoparticles, which act as much more efficient catalysts for water oxidation. Abstract : Comparison of homogeneous and heterogeneous catalysts in water oxidation is described by focusing on the conversion of various metal complexes into nanoparticles, which act as the actual reactive catalysts in water oxidation.